2013
DOI: 10.3390/medicina49040026
|View full text |Cite
|
Sign up to set email alerts
|

New Insights Into Pathophysiological Mechanisms Regulating Conventional Aqueous Humor Outflow

Abstract: The aim of the article was to overview the pathophysiology of the conventional outflow pathway, trabecular meshwork, and intraocular pressure and to discuss the options of future glaucoma treatment directed to improvement in aqueous outflow. The literature search in the Medline, Embase, and Cochrane databases from April to May 2012 was performed; a total of 47 articles analyzed. The diminished conventional pathway may be altered by several pathophysiological mechanisms like TM obstruction caused by transformin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…An alteration in the ECM may cause an increased resistance in the trabecular meshwork and a consequent decrease in outflow. [24,25] Our results support the idea that systemic inflammation may result in an increase in intraocular pressure. In line with our finding, Cellini et al [22] previously reported a significant association between systemic endothelial dysfunction and open-angle glaucoma.…”
Section: Discussionsupporting
confidence: 84%
“…An alteration in the ECM may cause an increased resistance in the trabecular meshwork and a consequent decrease in outflow. [24,25] Our results support the idea that systemic inflammation may result in an increase in intraocular pressure. In line with our finding, Cellini et al [22] previously reported a significant association between systemic endothelial dysfunction and open-angle glaucoma.…”
Section: Discussionsupporting
confidence: 84%
“… 30 Mucopolysaccharides of endothelial cells were related to macrophage function and were involved in the components of the ECM. 12 The change in the ECM might lead to an increase in the resistance of the trabecular meshwork, resulting in a decrease in outflow, 31 , 32 which might induce high IOP. Our results supported the view that systemic inflammation might lead to increased IOP.…”
Section: Discussionmentioning
confidence: 99%
“…The conventional drainage route of aqueous humor occurs via the trabecular meshwork (TM), Schlemm's canal (SC), collector channels, and aqueous veins and then streams into episcleral venous circulation. Appropriate secretion and regulation of aqueous humor are essential for normal eye function [ 2 ].…”
Section: Introductionmentioning
confidence: 99%